Pemberdayaan Kewirausahaan Ibu Rumah Tangga Melalui Pelatihan Pembuatan dan Pemasaran Keripik Singkong Pedas di kelurahan Waringinsari - Bramantiyo Eko Putro; Neng Viva (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Waringinsari Village in Takokak sub-district, Cianjur Regency, West Java has natural potential in the form of processing agricultural products. Waringinsari Village has a cassava plantation area of 2,000 m2 with a total harvest of 7.5 tons. These harvests have not provided benefits due to the lack of public knowledge about processing agricultural products. Demographic data of housewives in the village shows that 31 housewives do not have a job. Therefore, based on the problems encountered in the field, the authors carry out community service in the form of business assistance in the form of processing cassava plants into processed products of spicy cassava chips which are marketed both online and offline. The method used in this community partnership service (PKM) is to use the lecture and question and answer method, practice, and practice. This service activity succeeded in utilizing the cassava garden in Waringinsari village. Product sales are increasing every week by 15% for regular spicy and 12% for spicy jeletot. Housewife in Kp. Cicadas also know cassava processing and marketing so that it has additional income opportunities.